2017
DOI: 10.1126/sciadv.1701338
|View full text |Cite
|
Sign up to set email alerts
|

Size effects resolve discrepancies in 40 years of work on low-temperature plasticity in olivine

Abstract: When deforming by low-temperature plasticity, the strength of the mantle mineral olivine is controlled by its grain size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
129
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(148 citation statements)
references
References 61 publications
18
129
1
Order By: Relevance
“…The model calibrated in the previous section has several major implications for the strength of the lithosphere. First, as initially suggested by Kumamoto et al (), the grain size dependence of yield strength in olivine suggests that the strength of the coarse‐grained upper mantle may be lower by a factor of 5 than previous predictions based on experiments on fine‐grained olivine aggregates. However, the high degree of strain hardening observed in our experiments implies that, although the lithosphere may be initially weak at yield, it will strengthen quickly with progressive deformation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The model calibrated in the previous section has several major implications for the strength of the lithosphere. First, as initially suggested by Kumamoto et al (), the grain size dependence of yield strength in olivine suggests that the strength of the coarse‐grained upper mantle may be lower by a factor of 5 than previous predictions based on experiments on fine‐grained olivine aggregates. However, the high degree of strain hardening observed in our experiments implies that, although the lithosphere may be initially weak at yield, it will strengthen quickly with progressive deformation.…”
Section: Discussionmentioning
confidence: 98%
“…In Figure , we have compiled estimates of yield strength from previously published deformation experiments on olivine. Following Kumamoto et al (), we compare our results to previously published results as a function of the characteristic length scale of deformation, taken to be the grain size for experiments on polycrystals and the contact radius for indentation experiments. To compare data from our room‐temperature experiments to previous data from experiments at higher temperature, we have extrapolated previously published flow laws to room temperature and calculated the stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhong and Watts (2013) found that laboratory-derived LTP flow laws (e.g., Mei et al, 2010) must be weakened by a preexponential factor of 10 8 in order to reproduce the amplitude and wavelength of the observed flexure and depth distribution of seismicity at Hawaii. This has led to new experimental studies on the cause of the discrepancy between the field-based and laboratory studies on the LTP flow laws (Idrissi et al, 2016;Kumamoto et al, 2017). However, there are several limitations in the approach of Zhong and Watts (2013) that require further investigation.…”
Section: Introductionmentioning
confidence: 99%